(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Motor vehicle noise is one of the most common forms of man-made environmental pollution in urban conditions. Constant exposure to increased noise levels has a negative impact on human health, contributing to the development of conditions such as chronic fatigue, insomnia, decreased performance, as well as disorders of the cardiovascular, nervous and endocrine systems. The abstract views the sources of traffic noise, the mechanisms of its impact on the body, vulnerable groups of the population, as well as sanitary and hygienic standards and approaches to reducing noise pollution in urban environments. Special attention is paid to the issues of prevention and possible measures to protect public health from the adverse effects of noise pollution.